Controllable synthesis of Pd and Pt shells on Au nanoparticles with electrodeposition - Mohsen Elabbadi; Christina Boukouvala; Emilie Ringe (Scientific Reports)
Abstract Shells of Pd and Pt were synthesized on Au nanoparticles by electrodeposition, leading to controllable size and optical properties. This approach yielded core–shell structures with good homogeneity in size after the optimization of electrochemical parameters such as deposition current and charge transfer, as well as nanoparticle surface treatment. Dark field scattering microscopy and spectroscopy were used to track changes in the optical response of individual particles during deposition. The deposition of thin shells of Pd or Pt initially leads to a damping of the Au localized surface plasmon resonance which is followed by its redshift and an increase in scattering intensity. These changes were rationalized with numerical calculations and correlated with electron microscopy analyses revealing the morphology and thickness of Pd and Pt shells. This electrochemical approach provides a new pathway for the synthesis of bimetallic structures with catalytic surfaces.